2017
DOI: 10.1007/s11165-016-9580-4
|View full text |Cite
|
Sign up to set email alerts
|

Variables Affecting Secondary School Students’ Willingness to Eat Genetically Modified Food Crops

Abstract: A large-scale cross-sectional study (N = 4002) was set up to determine Flemish secondary school students' willingness to eat genetically modified food (WTE) and to link students' WTE to previously identified key variables from research on the acceptance of genetic modification (GM). These variables include subjective and objective knowledge about genetics and biotechnology, perceived risks and benefits of GM food crops, trust in information from different sources about GM, and food neophobia. Differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…The study results have shown strong correlations between the willingness to eat GMO food and the subjective knowledge as well as the objective knowledge. The results of the study have confirmed the need for supporting the knowledge base of the students with more education about biotechnology and GMO related topics in the early-stage [27]. Another study focused on millennial attitudes towards genetically modified food in the United States; it showed that respondents with a high level of education and knowledge about biotechnology had a higher level of willingness to purchase genetically modified food products.…”
Section: Literature Reviewmentioning
confidence: 55%
“…The study results have shown strong correlations between the willingness to eat GMO food and the subjective knowledge as well as the objective knowledge. The results of the study have confirmed the need for supporting the knowledge base of the students with more education about biotechnology and GMO related topics in the early-stage [27]. Another study focused on millennial attitudes towards genetically modified food in the United States; it showed that respondents with a high level of education and knowledge about biotechnology had a higher level of willingness to purchase genetically modified food products.…”
Section: Literature Reviewmentioning
confidence: 55%
“…“Factual knowledge” refers to concrete information and facts stored in an individual’s schema [43]. Other studies often label factual knowledge as objective knowledge (e.g., [7,15]). Such knowledge is often assessed by asking respondents to answer a series of true or false questions and computing the number of correct answers [42,44].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To date, the level of factual knowledge that consumers have on GMF in China is unclear. However, scholars suggest that factual knowledge of biotechnology and GMF is quite low in the US [40] and Belgium [7].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations